2007
DOI: 10.1038/sj.ejcn.1602840
|View full text |Cite
|
Sign up to set email alerts
|

L-ascorbic acid improves the serum folate response to an oral dose of [6S]-5-methyltetrahydrofolic acid in healthy men

Abstract: Objective: To investigate the effect of simultaneous administration of [6S]-5-methyltetrahydrofolic acid ([6S]-5-CH 3 H 4 PteGlu) with L-ascorbic acid (L-AA) on serum folate concentrations in healthy male subjects. Subjects and methods: A total of nine healthy male volunteers were recruited. Serum folate concentrations were measured before and up to 8 h after administration of each treatment (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…Beside the peak at T2, serum levels of folate were higher than baseline at the end of supplementation and even after the washout period in both groups. This is consistent with the results of Verlinde et al [38], who reported a maximum serum folate response in healthy men between 0.5 and 1.5 hours after folic acid sup-plementation with a significant improvement of serum folate concentrations during a cosupplementation with vitamin C. Stanger et al [39] published a homocysteine lowering effect with 5 mg folic acid and a significant improvement of peak reactivity of resistance vessels in coronary artery disease (CAD) patients without any effect on the total antioxidant status. Interestingly, in subjects with lower homocysteine baseline levels, with a median reduction of less than 2 μM, the total antioxidant status was significantly increased whereas the peak reactivity of resistance vessels was not affected.…”
Section: Discussionsupporting
confidence: 94%
“…Beside the peak at T2, serum levels of folate were higher than baseline at the end of supplementation and even after the washout period in both groups. This is consistent with the results of Verlinde et al [38], who reported a maximum serum folate response in healthy men between 0.5 and 1.5 hours after folic acid sup-plementation with a significant improvement of serum folate concentrations during a cosupplementation with vitamin C. Stanger et al [39] published a homocysteine lowering effect with 5 mg folic acid and a significant improvement of peak reactivity of resistance vessels in coronary artery disease (CAD) patients without any effect on the total antioxidant status. Interestingly, in subjects with lower homocysteine baseline levels, with a median reduction of less than 2 μM, the total antioxidant status was significantly increased whereas the peak reactivity of resistance vessels was not affected.…”
Section: Discussionsupporting
confidence: 94%
“…However, in our patient 3, long-term CH3-THF supplementation in a daily dose of 45 mg failed to correct the low CSF levels of CH3-THF (Table 2). Possible explanations to this lack of effectiveness include insufficient drug dosage and/or drug instability (Verlinde et al 2008). There are no reports of CH3-THF supplementation in patients with MTHFR deficiency.…”
Section: Available Treatmentsmentioning
confidence: 98%
“…Similarly, decreasing the consumption of SAM by giving exogenous creatine may be interesting. In addition, methods for optimizing treatments, for instance, high-dose of CH3-THF combined with ascorbic acid to prevent CH3-THF oxidation (Verlinde et al 2008), should be evaluated as tools for correcting the severe CH3-THF depletion in CSF of patients with MTHFR deficiency. When treatment is started late, the benefits are considerably more limited.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 99%
“…A total of 23 studies out of the original 5226 articles identified fit the full inclusion criteria and were appraised in this review. All studies provided quantitative data with 4 trials [19][20][21][22] using animal models and 19 studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] conducting human trials.…”
Section: Resultsmentioning
confidence: 99%
“…The studies varied in length from 8 h to 24 weeks. Twelve studies 19,20,22,[24][25][26]30,33,37,38,40,41 administered the intervention as an individual dose and measured outcomes at various intervals over the next 8-24 h. Seven [23][24][25][26]37,40,41 of those studies included a washout period of at least 1 week between the first intervention and the second. Three studies 25,26,33 also included a saturation period, where participants were predosed with folate before beginning the trial.…”
Section: Resultsmentioning
confidence: 99%